Flip chip joint-in-via architecture on flexible substrates with Au-Sn interdiffusion bonding - Lee, Teck Kheng (2008)
A new joint-in-via architecture has been developed with an instantaneous fluxless bonding know as SLICF (solid-liquid interdiffusion bonding by compressive force) for fine pitch microelectronic packaging. The SLICF bonding utilises a mechanical force to break the Sn oxide layer and allows the submerged body to interact with fresh molten solders to form bonds through solid liquid inter-diffusion. The solid-liquid kinetics of Au–PbSn and Au-SnAgCu solder are studied and quantified by the Au consumption rate. The Au consumption in solid liquid interdiffusion can be described as a two-stage kinetics; the instantaneous dissolution of Au into molten solder with the formation of an diffusion barrier followed by a diffusion kinetics through the diffusion barrier with time. The growth and shift of this diffusion barrier interfaces are governed by the Kidson’s interdiffusion model. The studies have shown that the rate of solid-liquid interdiffusion is found to be at least two orders of magnitude faster than solid-solid interaction. Field applications using existing packaging infrastructure has demonstrated the robustness of applying the SLICF bonding with the joint-in-via architecture for fine pitch flip-chip applications.